Investigation of Thermal Performance and Chemical Stability of Metal Infused Salt Hydrate Phase Change Material for Thermal Energy Storage - Pandey A.K.; Kumar R.R.; Samykano M.; Buddhi D.; Tyagi V.V. (Institute of Physics, 2024)
Thermal energy storage (TES) is a technique that is considered a very desirable technology with a high potential to overcome the gap between demand and supply. Phase change materials (PCMs) are considered to be a highly favourable thermal energy storage materials. Besides that, PCM has certain drawbacks, such as lower thermal conductivity and higher light transmission